The New Refugium Botanicum. Figures and Descriptions from Living Specimens, of Little Known or New Plants of Botanical Interest Grown at Lankester Botanical Garden. Maxillariella (Maxillaria) tenuifolia - Fernández Campos, Melania (2011)
Figures and Descriptions from Living Specimens, of little Known or New Plants of Botanical Interest Grown at Lankester Botanical Garden, University of Costa Rica